Estudo da microbiota vaginal por GRAM, pH, e níveis de lactato vaginais em lesões intraepiteliais cervicais e câncer de colo uterino - Magalhães, Christina Cordeiro Benevides (2020)
Introduction: Cervical cancer is a highly prevalent disease in the Ceara state’s population. Cervical cancer is closely correlated with the human papillomavirus (HPV) infection, which is considered the primary cause for the development of this type of cancer. Low- and high-grade squamous intraepithelial lesions are consequence of the cytopathic effect of human papillomavirus on the epithelial tissue of the uterine cervix. High-grade squamous intraepithelial lesions (HSILs) are considered to be precursors of cervical cancer. A balanced vaginal microbiome is important for maintaining the female genital tract health and for preventing vulvovaginal infections. Research has shown that HPV-infected women tend to have reduced lactobacilli and greater vaginal microbiota diversity. Local microbial communities can influence the acquisition and persistence of HPV infection, and the subsequent development of cancer. Lactobacilli acidify the vagina through the production of 1% lactic acid in a nearly racemic mixture of D and L isomers. Lactic acid is one of the main substances in the vaginal cavity, and it is responsible for maintaining the pH levels between 3.5 and 4.5. These pH levels are considered ideal for keeping female genital health. Lactobacilli produce lactic acid in its levogyre (L) and / or dextrogyre (D) form, while vaginal epithelial cell only produces lactic acid in the levogyre isomeric form (AcL-L), and in small concentrations. Each lactic acid isomer has specific properties in vaginal homeostasis. D-lactate has a greater protective activity against vaginal dysbiosis. L-lactate has immune properties such as stimulation of IL-23 / IL-17, induction of pro-inflammatory cytokines in epithelial cells when synthetic viral RNA is present, tumor angiogenesis induction, and bacterial growth inhibition. The great number of HPV infection and cervical cancer, and the impact of these diseases in the Brazilian female population reinforce the need and importance of research in this study area. Objective: To evaluate the microbiota vaginal, using Gram bacterioscopy and Nugent score, and to measure pH, D-lactate, and L-lactate in vaginal content of health women (no lesions), and of women diagnosed with LSIL, HSIL, cervical cancer. Methods: This observational, cross-sectional, quantitative and comparative study was conducted at the Ceara Cancer Prevention Institute during the period from February 2019 to October 2019. The randomly selected sample was composed of the vaginal content of 80 women with ages between 18 and 69 years old, with different diagnosis, including control, LSIL, HSIL, and cervical cancer. Before colposcopy, we made slides with vaginal content smears that were stained by the Gram technique for reading observing the Nugent criteria. We have also measured pH on the right lateral vaginal wall using an indicator tape positioned in direct contact with the vaginal mucosa. In addition, we collected vaginal content for dilution in a plastic tube containing 1 ml of PBS. The material was subsequently processed to measure D and L-lactates. Statistical analysis: Statistical analysis used the software GraphPad Prism® and SPSS®. The level of statistical significance considered for all analyzes was p-value <0.05. Results: The 80 patient sample was stratified into the following diagnostic groups: women without intraepithelial lesions or negative (23/ 28.75%), LSIL (10/ 12.5%), HSIL (45/ 56, 25%), CEC (2/ 2.5%). The mean age of the negative group was 46.04 years old, of the LSIL group was 41.7 years old, of the HSIL group was 37.95 years old, and of the CEC group it was 52.5 years old. There were no observed statistically significant results when correlating the studied diagnosis with the vaginal microbiota morphotypes, with the mean pH, and with the D-lactate. However, it was possible to demonstrate with statistically significant results (p-value <0.0001) that women diagnosed with HSIL plus cancer diagnosis have a higher amount of L-lactate in the vaginal fluid when compared to the control group. Conclusions: This finding indicates that the L-lactate plays an important role in the process of cervical carcinogenesis, requiring further investigation for better characterization and analysis.